Synthesis and Mesomorphic and Electrical Investigations of New Furan Liquid Crystal Derivatives - Al-Mutabagani, Laila A.; Alshabanah, Latifah A.; Gomha, Sobhi M.; Abolibda, Tariq Z.; Shaban, Mohamed; Ahmed, Hoda A. (Frontiers in Chemistry, 2021)
New homologues set liquid crystalline materials, based on furfural derivatives namely, (E)-4-((furan-2-ylmethylene)amino)phenyl 4-alkoxybenzoate (Fn), were synthesized and investigated for their mesomorphic and optical characteristics. The prepared homologues series constitutes three derivatives that bearing different terminal flexible alkyl chain length that varies between 6 and 12 carbons and attached to the phenyl ring linked to the ester group. A furfural moiety is introduced into the other terminal of the molecular structure. Mesomorphic characterizations of the prepared derivatives were measured using differential scanning calorimetry (DSC) and polarized optical microscopy (POM). Molecular structures were elucidated via elemental analyses, FT-IR, and NMR spectroscopy. DSC and POM measurements showed that all the synthesized furfural derivatives are purely nematogenic exhibiting enantiotropic nematic (N) mesophase, except for the longest chain derivative (F12) that is dimorphic possessing monotropic smectic A phase and enantiotropic N mesophase. The results indicated that the incorporation of the heterocyclic furfural ring into the molecular skeleton affected both the mesophase stability and its temperature range of investigated homologue. Analysis of the optical properties revealed that the shortest chain compound (F6) possesses two direct band gaps, at 2.73 and 3.64 eV, in addition to higher absorption than the higher homologues, F10 and F12. On the other hand, all the synthesized homologues (Fn) showed Ohmic behaviors with electric resistances in the GΩ range. The values of the electrical resistances are 103.71, 12.91, and 196.85 GΩ@0.05V for F6, F10, and F12, respectively.